SAT0150 Optimising Treatment with TNF Inhibitors in Rheumatoid Arthritis with Different Dose Tapering Strategies: The Opttira Trial. (9th June 2015) - Galloway, J.B.; Kingsley, G.; Ma, M.; Lorente-Canovas, B.; Cope, A.; Ibrahim, F.; Scott, D.L.
Abstract : Background: Treating rheumatoid arthritis (RA) with tumour necrosis factor inhibitors (TNFi) involves inducing then maintaining responses. Currently both use identical TNFi dosing regimens. Objectives: OPTTIRA, a pragmatic, multicentre, 12-month randomised controlled trial, evaluated if tapering TNFi doses causes loss of response. Methods: We recruited RA patients receiving etanercept or adalimumab plus a DMARD with stable low disease activity (DAS28 less than 3.2 for over 3 months). We excluded patients with serious concomitant illness or taking high-dose steroids (more than 10mg prednisolone daily). Initially (months 0-6) patients were randomised to three groups: controls received constant TNFis; one experimental group tapered TNFis by 33% and the other by 66%. If tapering caused flares (increase in DAS28 more than or equal to 0.6 plus 1 or more swollen joints out of 66 joints) TNFis were restarted. Subsequently (months 6-12) controls tapered TNFis and experimental groups discontinued TNFis. The outcomes comprised flare rates and DAS28 scores after 6 months constant or tapered TNFis. Results: 227 patients were screened at 20 UK centres, 103 were randomized, 97 were treated in months 0-6 and 74 in months 6-12. With TNFis tapering: flares occurred in 14% of controls, 13% patients tapered by one-third and 37% tapered by two-thirds. Flares were increased with two-thirds tapering with odds ratio 4.1; 95% (CI 1.3, 14.5) compared with one-third tapering. Post-tapering flares resolved when TNFis were restarted. There were no significant differences in HAQ with either tapering strategy (Table ) at six months. Of 47 patients who tapered then stopped TNFis. 21/47 (45%) succeeded without flaring and their final mean DAS28 scores after stopping treatment were 2.2 (95% CI 1.6, 2.9). Evaluating harms showed one patient withdrew for TNFis-related toxicity (control) and four patients had serious adverse events (control 1; experimental 3); none were related to TNFis tapering. Conclusions: Good responses to TNFi are maintained after TNFi doses are tapered by one-third. Tapering by two-thirds results in more flares, but these respond to restarting TNFis and did not adversely affect disability progression. Some patients maintain responses after stopping TNFis. Lowering TNFi maintenance doses retains responses at substantially reduced drug costs. Adopting this strategy should enhance biologic cost-effectiveness. Disclosure of Interest: None declared